Relationship and Effects of Community Problems on Anxiety and Suicide: A Case-Control Psychological Autopsy Study. Issue 1 (January 2021) - Lyu, Juncheng; Ding, Li; Zhang, Jie
Abstract : Abstract: This study aimed to explore the relationship and the effects of community problems on anxiety and suicide. Data were from a case-control psychological autopsy study (392 suicides and 416 community living controls) carried out in 16 rural counties from three provinces in China. The World Health Organization Suicide Prevention–Multisite Intervention Study on Suicidal behaviors scale of community stress and problems and Spielberger State-Trait Anxiety Inventory were used to measure the community problems and trait anxiety. Spearman's correlation and multivariable regression methods were used to probe the effect of community problems on anxiety and suicide. There were 12 and 6 community problems correlated with anxiety ( r s = 0.169, p < 0.001) and suicide ( r s = 0.081, p = 0.022), respectively. Medical care, alcohol abuse, superstition, and job security were important community problems for anxiety and suicide. Community problems had stronger correlation with anxiety than suicide. It might be an effective method to reduce anxiety and suicide risk by solving different community problems.